2005
DOI: 10.1111/j.1365-201x.2004.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional intestinal adaptations in Na+,K+‐ATPase in experimental colitis and the contrasting effects of interferon‐γ

Abstract: The increase in ileal Na+,K+-ATPase activity upstream to the lesioned colonic mucosa, where Na+,K+-ATPase activity was markedly reduced, might indicate a compensatory process to counteract the decrease in water and electrolyte absorption at the colonic level. This decrease in colonic Na+,K+-ATPase activity is likely not related to INF-gamma-induced downregulation of Na+,K+-ATPase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The Na + -K + -ATPase, which is found exclusively in the pancreatic acini, plays a central role in pancreas electrolyte regulation and in the pathogenesis of pancreatic inflammation [54]. Since decreased Na + -K + -ATPase activity most likely reflects a diminished number of enzyme molecules due to a loss of Na + -K + -ATPase-containing mucosal cells [55], consequently, it also indicates severe mucosal inflammation and the loss of physiological function. Since proanthocyanidin treatment in the present study reversed cerulein-induced increment in MPO and reduction in Na + -K + -ATPase enzyme activity, it indicates that proanthocyanidin alleviates the pancreatic injury by preserving membrane structure.…”
Section: Discussionmentioning
confidence: 99%
“…The Na + -K + -ATPase, which is found exclusively in the pancreatic acini, plays a central role in pancreas electrolyte regulation and in the pathogenesis of pancreatic inflammation [54]. Since decreased Na + -K + -ATPase activity most likely reflects a diminished number of enzyme molecules due to a loss of Na + -K + -ATPase-containing mucosal cells [55], consequently, it also indicates severe mucosal inflammation and the loss of physiological function. Since proanthocyanidin treatment in the present study reversed cerulein-induced increment in MPO and reduction in Na + -K + -ATPase enzyme activity, it indicates that proanthocyanidin alleviates the pancreatic injury by preserving membrane structure.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ decreases the NKA activity possibly through PGE 2 (95,100) and to a smaller extent also lowers the expression of the Na/K/Cl symporter (95), whereas IL-1␤ downregulates NKA but stimulates Na/K/Cl symporter (and thus Cl Ϫ secretion) (76). Lipoxygenase products (HETEs and LTB 4 ) did not affect colonic NKA activity (3), whereas TGF-␤ and NH 2 Cl increased it (93,121). NO, found in high concentrations in IBD (19), also inhibits NKA activity in T84 cells (134).…”
Section: Downregulation Of Namentioning
confidence: 99%
“…Three proinflammatory cytokines are known to downregulate NKA: IFN-␥, TNF-␣, and IL-1␤. T cell-produced IFN-␥ (18,93,134) is thought to activate the PKC downstream STAT1 phosphorylation and Raf-1, MEK, ERK2, and p38 MAPK (92), but there is conflicting evidence regarding its dependency of NO (134,158). TNF-␣ decreases the NKA activity possibly through PGE 2 (95,100) and to a smaller extent also lowers the expression of the Na/K/Cl symporter (95), whereas IL-1␤ downregulates NKA but stimulates Na/K/Cl symporter (and thus Cl Ϫ secretion) (76).…”
Section: Downregulation Of Namentioning
confidence: 99%
“…As in other transport enzymes within the erythrocyte membrane, Na + -K + -ATPase enzyme is also known to depend on the presence of membrane phospholipids for its activation. [35,36] We found that the Na + -K + -ATPase activity level was significantly higher in the ALA-treated pancreatitis group compared to the saline-treated group (p<0.01).…”
Section: Histologic Preparation and Analysismentioning
confidence: 63%